Kontribusi Kekuatan Otot Lengan terhadap Hasil Tolak Pelurusiswa Smp Negeri 07 Rambah Samo Kabupaten Rokan Hulu - Hendri Mulyadi (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2020)
The problem of this research is the low ability of the students to shoot the results of SMP Negeri 07 Rambah Samo Rokan Hulu Regency which is influenced by the weak strength of the arm muscles in repelling bullets. The purpose of this study was to determine the contribution of arm muscle strength to the shot put results of students at SMP Negeri 07 Rambah Samo, Rokan Hulu Regency.This type of research is a correlation that looks at the extent of the contribution of arm muscle strength to the results of the shot. The population of this study were 29 students of SMP Negeri 07 Rambah Samo Rokan Hulu Regency. The sample was taken using total sampling technique. The research instrument for arm muscle strength was the push up test. As for the results of the shot put down, the measurement is done by carrying out the shot put test. The analysis technique used is manual product moment correlation.The results showed, 1) arm muscle strength was categorized as good with a value of 56.31%, 2) the results of the shot were categorized as good with a value of 43.69%, 3) data analysis showed that the value of rxy (rhitung) was 0.573 with r table 0.532 then the r count is obtained from the r table, so there is a contribution of 33%. There is a contribution between arm muscle strength to the results of the shot at SMP Negeri 7 Rambah Samo Rokan Hulu Regency. Keywords: arm muscle strength, shot put results